THE EFFECTS OF ANGIOTENSIN CONVERTING ENZYME INHIBITION AND ALPHA 1-ADRENERGIC RECEPTOR BLOCKADE ON HAEMOSTASIS AND INFLAMMATION IN MILD-TO-MODERATE HYPERTENSION. (June 2018) - Ekholm, M.; Jekell, A.; Wallén, N.H.; Gigante, B.; Kahan, T.
Abstract : Objective: Hypertension is associated with oxidative stress and low-grade chronic inflammation, contributing to phenotypical alterations of the endothelium to a proconstrictive, proinflammatory and prothrombotic phenotype. Antihypertensive therapy improves vascular structure and function, and reduces cardiovascular complications. However, the relative contribution of antihypertensive therapy on vascular inflammation, thrombogenic mechanisms, and endothelial dysfunction remains unclear. We have previously demonstrated that treatment of hypertensive patients with ramipril, an ACE inhibitor, reduced thrombin generation compared to placebo treatment. This study aimed to extend these observations and to investigate the possible contribution of blocking the RAAS on haemostasis and systemic inflammation beyond the effects of lowering blood pressure. Design and method: We examined 59 individuals with mild-to-moderate hypertension randomized to receive double blind ramipril 10 mg od or the alpha 1-adrenergic receptor blocker doxazosin 8 mg od for 12 weeks. Haemostasis (plasminogen activator inhibitor-1 activity, tissue plasminogen activator antigen, thrombin-antithrombin complex, and thrombin generation by calibrated automated thrombogram) and inflammatory markers (interleukin-6, soluble interleukin-6 receptor, interleukin-8, tumor necrosis factor-alpha, monocyte chemoattractant protein-1, and C-reactive protein) were assessed. Results: Treatment reduced blood pressure in both groups. Thrombin-antithrombin complex decreased by treatment, and this was dependent on a reduction in thrombin-antithrombin complex in the ramipril group alone (figure). Changes in thrombin-antithrombin complex by treatment did not relate to changes in blood pressure. There were no changes in plasminogen activator inhibitor-1 activity, while tissue plasminogen activator antigen increased by ramipril and decreased by doxazosin. Only minor changes were observed in systemic inflammation by treatment. Figure. No caption available. Conclusions: These results extend our previous findings to suggest that antihypertensive treatment with ramipril reduces thrombin generation beyond the effects on blood pressure reduction alone. Thus, drugs blocking the RAAS may reduce atherothrombotic complications beyond their effects to reduce blood pressure. Furthermore, doxazosin might have beneficial profibrinolytic effects. The antihypertensive treatment effects on inflammatory markers, however, were small.